Evaluation of alpha amylase and peroxidase in saliva of pregnant women - Al-zahraa J Jassim; Zainab A Al Dhaher; Faten M Allyan (College of Dentistry/ University of Baghdad, 2023)
Background: Pregnancy is a natural physiological state that involves several biochemical modifications. Saliva is consisted of many types of proteins such as salivary alpha amylase and salivary peroxidase that might be affected by pregnancy. The former enzyme is considered one of the most prevalent proteins that is released by highly differentiated epithelial acinar cells and has been shown to have enzymatic activities while the latter has been approved that it  has a significant role in oral health. The purpose of this study was to the evaluate the salivary levels of alpha-amylase and peroxidase in pregnant and non-pregnant women. Materials and Methods: Sixty pregnant women were grouped according to the pregnancy trimesters. The first group involved 20 women in the 1st trimester, 2nd group represented by 20 women in the 2nd trimester while the 3rd group involved the rest who were in the 3rd trimester. In addition to 20 married non pregnant women as a control group. Salivary samples were collected from each group to compare the salivary level of alpha-amylase and peroxidase using sandwich enzyme-linked immune-sorbent assay. Results: 2nd and 3rd groups illustrated high significant level of theses enzymes in comparison with the control group. However, the first group demonstrated non-significant differences in the level of tested enzymes when compared to that of the control group. Conclusion: It was concluded that the salivary alpha amylase and salivary peroxidase have higher levels in pregnant women with dramatic increase for those in the third trimester.